2018
DOI: 10.3201/eid2410.171891
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Dynamics of Highly Pathogenic Avian Influenza Virus A(H5Nx) Clade 2.3.4.4, North America, 2014–2015

Abstract: Eurasia highly pathogenic avian influenza virus (HPAIV) H5 clade 2.3.4.4 emerged in North America at the end of 2014 and caused outbreaks affecting >50 million poultry in the United States before eradication in June 2015. We investigated the underlying ecologic and epidemiologic processes associated with this viral spread by performing a comparative genomic study using 268 full-length genome sequences and data from outbreak investigations. Reassortant HPAIV H5N2 circulated in wild birds along the Pacific flywa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
5
35
0
Order By: Relevance
“…Additionally, other variables that represent potential migratory stopover habitats, such as Important Bird Areas and agricultural land, were not supported within the model, suggesting that if wild birds contributed to HPAI dispersal within the Midwest, their role was limited. This further supports previous studies, which indicated that the midwestern portion of the outbreak was driven by inter-farm transmission [11,12,14]. Several mechanisms have been proposed to explain HPAI transmission between farms during the 2015 outbreak, including equipment sharing, personnel overlap, and aerosolization.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, other variables that represent potential migratory stopover habitats, such as Important Bird Areas and agricultural land, were not supported within the model, suggesting that if wild birds contributed to HPAI dispersal within the Midwest, their role was limited. This further supports previous studies, which indicated that the midwestern portion of the outbreak was driven by inter-farm transmission [11,12,14]. Several mechanisms have been proposed to explain HPAI transmission between farms during the 2015 outbreak, including equipment sharing, personnel overlap, and aerosolization.…”
Section: Discussionsupporting
confidence: 90%
“…Whole genome HPAI H5N2 sequences collected, isolated and sequenced by the United States Department of Agriculture (USDA) during the 2014-2015 North American HPAI outbreak served as the basis for the analyzed data set. Full description of their collection and sequencing has been reported elsewhere [14]. A subset of this sequence data was selected to better investigate the farm-to-farm transmission dynamics of the midwestern portion of the HPAI H5N2 outbreak.…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite frequent reports of wild birds on the grounds and within barns of HPAI-positive turkey premises (10), a case-control study found no significant difference in exposure to wild birds between positive turkey premises and matched controls (11). Similarly, one phylodynamic analysis found no evidence of continued HPAI introductions into the Midwestern poultry industries (12), but other models have suggested multiple introductions (13,14). Geographic and environmental variables, such as human population, agricultural, climatological, and ecological measures, may help explain farm-to-farm transmission observed within the poultry industries.…”
Section: Introductionmentioning
confidence: 99%